Faktor yang mempengaruhi sikap beragama: perspektif edwin diller starbuck - Tamami, Abi Syamsudin (Maliki Interdisciplinary Journal, 2025)
Religious attitude is an important aspect of individual life that is influenced by psychological, social, and biological factors. Edwin Diller Starbuck, as a pioneer of the psychology of religion, emphasized that religious experience can be analyzed empirically through a scientific approach. This article aims to examine Starbuck's theory regarding the development of religious consciousness as well as the main factors that influence a person's religious attitudes. The results show that religious conversion often occurs during adolescence, influenced by social environments such as family and community, as well as psychological aspects such as spiritual reflection. In addition, biological changes also play a role in shaping an individual's religious experience. By understanding these factors, this study can contribute to the psychology of religion and build more moderate and inclusive religious attitudes in a diverse society.